A novel kinked rebar configuration for simultaneously improving the seismic performance and progressive collapse resistance of RC frame structures. (15th September 2017) - Feng, Peng; Qiang, Hanlin; Qin, Weihong; Gao, Meng
Highlights: A "ONE-STONE-TWO-BIRDS" novel configuration using kinked rebar in RC frame structures is presented. The mechanical behavior of the kinked rebar is studied. FE analyses of RC frames with kinked rebar are presented. Abstract: Lateral collapses due to earthquakes and progressive collapses due to the sudden destruction of the columns are two of the most commonly encountered failure mechanisms for buildings. To simultaneously improve the seismic performance and the progressive collapse resistance of reinforced concrete (RC) frame structures, this paper presents a novel method using kinked rebar. Kinked rebar has a large deformability because it can be gradually straightened under a tension force, and it can be placed near the inflection points in beams under uniform vertical loads in RC frame structures. First, uniaxial tensile tests were performed to study the equivalent stress-equivalent strain relation and the deformation mode of the kinked rebar. Second, three-point and four-point bending tests were performed to investigate the load-deflection relationship and the failure modes of simply supported beams with local kinked rebar. Third, numerical simulations based on the fiber beam model were conducted to study the seismic behavior and progressive collapse resistance performance of a six-story RC frame with local kinked rebar in the beams. The mechanical behavior of the new beam section with kinked rebar was used to relocate the plastic hinges and to successfully improve the calculated progressive collapse resistance of the RC frame.